Pengaruh Persepsi Kemudahan Dan Persepsi Keamanan Terhadap Keputusan Penggunaan E-Wallet Shopeepay Di Kalangan Generasi Millenial ( Studi Pada Mahasiswa Manajemen UNISMA Angkatan 2018) - Roki Candra Pitura; N. Rachma (UNIVERSITAS ISLAM MALANG, 2022)
Abstract Instruments or means of payment have undergone changes, starting from conventional payment instruments in the form of metal and paper, now developing in a more practical form, namely electronic payment instruments. The purpose of this study was to determine the effect of perceived convenience and security on the decision to use shopeepay e-wallet. The type of research is quantitative research with a population of management students at the Islamic University of Malang Batch 2018 totaling 565 students who use the shopeepay application and purposive sampling is carried out and a test of 100 respondents is gotten. The information were then examined by numerous straight relapse test with the assistance of SPSS 25 programming. The outcomes showed that apparent straightforwardness altogether affected the choice to utilize shopeepay e-wallet. In like manner, the impression of safety to some degree altogether affects the choice to utilize shopeepay e-wallet. The variable impression of comfort and security all the while altogether affects the choice to utilize shopeepay e-wallet. Keywords: Perception of Ease, Security Perception, Usage Decision, e-wallet, Shopeepay